Uma proposta de formação colaborativa sobre o ensino de ciências: a importância da reflexão para o desenvolvimento profissional docente - Gomes, Bruna Cristina Carvalho (Universidade Federal de São Carlos, 2019)
The current sociocultural reality requires that people possess knowledge about various subjects, that they are able to analyze causes and effects and they can position themselves in the face of social debates. On the other hand, Brazilian education presents several types of problems, including the shortcomings of teacher education and the constant challenge of learning, with oneself and with others. The training of citizens with values and the knowledge necessary for critical participation can be promoted through the relations between Science, Technology and Society (STS) in science teaching, from the early years of elementary school and it becomes a great ally to children's literacy and development of children. To achieve this aim, teachers must understand their theoretical and methodological assumptions for the development of thematic activities with their students. Due to the relevance of teacher training, a partnership was established between the researcher and an experienced first year teacher of Elementary School with the objective of analyzing the results of a collaborative training proposal, based on the reflection about science teaching in the STS perspective for professional teacher development. Thus, this research was based on the following question: What are the contributions of a proposal of collaborative training based on reflection on the teaching of science in the STS perspective for professional teacher development? For the constitution of the collaborative work, eight meetings were held with discussion of theoretical references on reflective teacher and STS teaching approach, as well as for the planning and development of a teaching situation, from this perspective, about planetary system. The following instruments were used to compile data: transcription of the videos of the meetings, written records of the questionnaires (initial and final), records of the professional trajectories and the diaries of the researcher and the teacher. By characterizing it as a qualitative research, we opted for the discursive textual analysis, in which the texts were: separated by their meanings, categorized, analyzed and interpreted. Thus, three categories of analysis were identified. The first one covers all the situations in which there was the reflection on the practice itself in the teaching of Sciences. The second one refers to the discussions related to the theoretical reference about reflexive teacher and the teaching of sciences emphasizing STS, that is, reflection on the relation theory and practice. The third covers a discussion concerning reflection on the teaching profession. In summary, we consider that the collaborating teacher had the opportunity to analyze and reflect on the practice itself as well as the conditions of the teaching system to which it belongs, identifying factors that affect its methodological choices. Among the contributions of the formative proposal, we highlight the recognition of the learning process of teaching as a “continuum” throughout the career; the importance of interaction with peers to favor the attribution of meaning to new experiences, as well as previous experiences. We also emphasize the promotion of reflections in a systematic, rigorous and disciplined way that requires the valorization of attitudes of both parties and favors professional teacher development.
A proposed collaborative training on science teaching: the importance of reflection for teaching professional development
Keywords: Trabalho colaborativo; Reflexão; Ensino de Ciências; Desenvolvimento profissional docente; Collaborative work; Science teaching; Reflection; Teaching professional development; CIENCIAS HUMANAS::EDUCACAO::ENSINO-APRENDIZAGEM::METODOS E TECNICAS DE ENSINO